The Qur'an a historical-critical introduction - Sinai, Nicolai 1976- (Edinburgh University Press, 2017)
An accessible and up-to-date introduction to the study of the Qur'an in its historical contextThe Qur'an represents both Islam's historical point of origin and its scriptural foundation, inaugurating a new religion and, ultimately, a new civilisation. Yet the text itself can be difficult to understand, and the scholarship devoted to it is often highly technical. This comprehensive introduction to the basic methods and current state of historical-critical Qur'anic scholarship covers all of the field's major questions, such as: Where and when did the Qur'an emerge? How do Qur'anic surahs function as literary compositions? How do the Qur'an's main themes and ideas relate to and transform earlier Jewish and Christian traditions?Reading this book will give you the tools needed to work with and understand this vital but complex text.Key FeaturesEngages with alternative arguments and perspectives and offers a rigorously historical perspective on controversial topics such as Qur'anic militancySynthesises a literary approach to the Qur'an with detailed attention to its engagement with Jewish and Christian traditionsProvides specific and accessible examples, including exemplary analyses of several Qur'anic surahs and passages and a case study of the Qur'anic Adam narrativesOffers a rigorously historical perspective on controversial topics such as Qur'anic militancy and the Qur'an's engagement with Judaism and ChristianityIncludes figures and tables highlighting key facts
Keywords: Koran; Historische Kritik